Les archives de la répression de 1945 à 1971 déclassifiées - AfricaNews (Africanews, 2023)
Paris livre ses archives classifiées à la commission d'historiens pour faire la lumière sur le rôle de la France dans la violente répression ayant visé les indépendantistes.
Cameroon
Keywords: 2023-10 November

Senegal: Invaluable archives destroyed during unrest at Dakar's main university - AfricaNews (Africanews, 2023)
Students from Dakar's Cheikh Anta Diop University are attempting to rescue some 200,000 university documents that were burnt during the deadly protests following the two-year prison sentence handed down to opponent Ousmane Sonko.
Senegal
Keywords: 2023-06 June